What is the problem of universals? - Rodriguez-Pereyra, G (2000)
In this article I address the Problem of Universals by answering questions about what facts a solution to the Problem of Universals should explain and how the explanation should go. I argue that a solution to the Problem of Universals explains the facts the Problem of Universals is about by giving the truthmakers (as opposed to the conceptual content and the ontological commitments) of the sentences stating those facts. I argue that the sentences stating the relevant facts are those like 'a has the property F', that is, sentences stating that a particular has a certain property. Finally I show how answering these questions in this way transforms the Problem of Universals, traditionally conceived as the One over Many, that is, the problem of explaining how different particulars can have the same properties, into the Many over One, that is, the problem of explaining how the same particular can have different properties. The Problem of Universals is the problem of the Many over One. © Oxford University Press 2000.